ANALISIS PENGARUH JUMLAH UNIT USAHA, INVESTASI, DAN UPAH MINIMUM TERHADAP PENYERAPAN TENAGA KERJA INDUSTRI KECIL DI KABUPATEN MALANG - Saputra, Rio Dhuwi; Pratomo, Devanto Shasta (Jurnal Ilmiah Mahasiswa FEB, 2013)
This paper is made with the aim to explain how the effect of business units, investment, and the minimum wage on  labor  in  small industries Malang districts. Then to explain the effect of each independent variable which business units, investment, and the minimum wage on  labor. Dependent variable, we used multiple linear regression analysis model by analyzing the classical assumption that includes: normality test, heteroscedasticity, multicollinearity test,  and the autocorrelation test. It is also done some statistical analysis is by T test, F  test, and test R2. The results showed that each of the independent variables are business units, investment, and the minimum wage significantly affect the dependent variable is labor. while among some of the most influential independent variables on the dependent variable is the business unit.Keyword: Business units, Investment, Minimum wage on labor, Small industries